Progressão do grau de incapacidade física e da autodeclaração de cura, no período pós-término do tratamento da hanseníase, em área coberta pela atenção básica à saúde no Brasil - Ramos, Aleksandra Rosendo dos Santos (2019)
Introduction - Leprosy is a curable disease through chemotherapy (MDT). However, physical disabilities as a result of neural damage may progress in the post-treatment period.Leprosy is a curable disease through the treatment of chemotherapy (MDT). The physical disabilities and health problems related to sequelae after discharge may interfere with the self-reported of leprosy cure. Objective - To analyze the risks associated with the development of physical disabilities and those related to the self-declaration of cure of leprosy in the post-treatment period, in Cáceres-MT from 2000 to 2017. Methods - Study developed in three stages: 1- Documentary study on the technical guidelines for the prevention of leprosy in Brazil, by means of historical review in the time line; 2- Retrospective cohort study on the risk of progression of physical disability due to leprosy in the post-discharge period due to cure in the hyperendemic area of the disease; 3- Cross-sectional study on the selfreported of cure of leprosy, in the post-high period, in Cáceres, Mato Grosso, endemic region of the disease. The analyzes were stratified according to operational, clinical and socioeconomic variables. Results - The publications of prevention of FI coordinated by the Ministry of Health were adequate over the years from a conceptual, political, strategic and assistance point of view. They covered, mainly, the activities of neurological evaluation and the degree of physical incapacity, techniques of prevention of incapacities and self-care. The survival curve shows that after 10 years of treatment with multidrug therapy, the probability of progression of the degree of physical disability was 30% and in 15 years 35%. Factors associated with the self-reported of non-cure of leprosy were related to health complaints related to the sequelae of the disease, OR = 3.72 (1.81 - 7.62), and the degree of physical incapacity in post-discharge, grade 1 OR = 2.58 (1.04 - 6.36) and grade 2 OR = (2.97-20.12). Conclusion - The risk of worsening physical disabilities due to leprosy after 15 years affects more than one-third of individuals on discharge for cure. One in four people cured of leprosy consider themselves sick. Health services should be organized not only for the diagnosis and supply of multidrug therapy but for all aspects involving the disease.